Comparing the Foreign Media Representation Between Turkey and Indonesia Based on Online Media Newspapers - Dela Anjelawati; Lely Arrianie (Dinasti International Journal of Education Management And Social Science, 2023)
Turkey-Indonesia relations can be traced back to the Ottoman Empire. For many years, bilateral cooperation outside Turkey and Indonesia continue to work together within the framework of international and regional organizations. Media studies are expected to provide benefits in the increased relation between the two countries. Therefore, it is interesting to analyse how the media representation in Indonesia and Turkey construct the image about one and another. This work analyses image, and news value in order to understand the media representation of Turkey and Indonesia. this study will observe the news representations of Indonesia and Turkey in terms of their representations as country, country's news actors, and relation between Turkey and Indonesia. This study will examine how Indonesia and Turkey are represented in Turkey in the press in Indonesia. Specifically, theoretical perspectives are used to understand news production and understanding processes. These perspectives relate to Critical Discourse Analysis (CDA) as the research approach of this study.